A Mixed Methods Study of the Association of Non-Veterans Affairs Care With Veterans' and Clinicians' Experiences of Care Coordination. Issue 8 (August 2020) - Benzer, Justin K.; Gurewich, Deborah; Singer, Sara J.; McIntosh, Nathalie M.; Mohr, David C.; Vimalananda, Varsha G.; Charns, Martin P.
Abstract : Background: Poor coordination between the Department of Veterans Affairs (VA) and non-VA care may negatively impact health care quality. Recent legislation is intended to increase Veterans' access to care, in part through increased use of non-VA care. However, a possible consequence may be diminished patient experiences of coordination. Objective: The objective of this study was to determine VA patients' and clinicians' experiences of coordination across VA and non-VA settings. Design: Observational mixed methods using patient surveys and clinician interviews. Sampled patients were diagnosed with type 2 diabetes mellitus and either cardiovascular or mental health comorbidities. Participants and Measures: Patient perspectives on coordination were elicited between April and September 2016 through a national survey supplemented with VA administrative records (N=5372). Coordination was measured with the 8-dimension Patient Perceptions of Integrated Care survey. Receipt of non-VA care was measured through patient self-report. Clinician perspectives were elicited through individual interviews (N=100) between May and October 2017. Results: Veterans who received both VA and non-VA care reported significantly worse care coordination experiences than Veterans who only receive care in VA. Clinicians report limited information exchange capabilities, which, combined with bureaucratic and opaque procedures, adversely impact clinical decision-making. Conclusions: VA is working through a shift in how Veterans receive health care by increasing access to care from non-VA providers. Study findings suggest that VA should prioritize coordination of care in addition to access. This could include requiring monitoring of patient-experienced care coordination, surveys of referring and consulting clinicians, and pilot testing and evaluation of interventions to improve coordination. Abstract : Supplemental Digital Content is available in the text.